2017
DOI: 10.1128/jvi.01543-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Approach To Identify Key Amino Acids in Low Susceptibility of Rabbit Prion Protein to Misfolding

Abstract: Prion diseases, or transmissible spongiform encephalopathies (TSEs), are a group of rare progressive neurodegenerative disorders caused by an abnormally folded prion protein (PrP). This is capable of transforming the normal cellular prion protein (PrP) into new infectious PrP Interspecies prion transmissibility studies performed by experimental challenge and the outbreak of bovine spongiform encephalopathy that occurred in the late 1980s and 1990s showed that while some species (sheep, mice, and cats) are read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 87 publications
(101 reference statements)
0
31
1
Order By: Relevance
“…Protein misfolding cyclic amplification treated samples were incubated with 85‐200 μg/mL of protease K (PK) for 1 hours at 42°C with shaking (450 rpm) as described previously . Digestion was stopped by adding electrophoresis Laemmli loading buffer and the samples were analyzed by Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…Protein misfolding cyclic amplification treated samples were incubated with 85‐200 μg/mL of protease K (PK) for 1 hours at 42°C with shaking (450 rpm) as described previously . Digestion was stopped by adding electrophoresis Laemmli loading buffer and the samples were analyzed by Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…It could be argued that the role of consensus amino acids in the different sensitivity of mammalian orthologues against disease might be a rare situation (let’s say, only for AGT and NQO1). However, it is well known that some mammalian species are particularly more resistant against disease-associated mutations than humans, which is likely associated to small divergences in the sequence and properties of the corresponding proteins [ 19 , 20 , 81 , 82 ]. Without a need to invoke inter-species differences in gene expression, regulation or protein homeostasis capacities, this situation has been investigated at the protein (sequence) level in this and other grounds, and referred to as compensated pathogenic deviation (CPD).…”
Section: Evolutionary Divergence In Key Compensatory Consensus Amimentioning
confidence: 99%
“…The focus on rabbit PrP brought forth a number of studies to uncover the mechanisms mediating resistance to TSE. Though over a decade apart, two studies emerged as highly similar in goals ( Vorberg et al, 2003 ; Eraña et al, 2017 ). These studies identified 22 amino acid differences between full-length rabbit and mouse PrP, and set out to determine which residues impact prion transmissibility by complementary approaches.…”
Section: Purified and In Vitro Models Of Resistantmentioning
confidence: 99%
“…The assay consisted on determining which substitutions inhibited the ability of recPrP from replicating prions. More recently, the Castilla group used recombinant rabbit PrP carrying mouse-specific changes ( Eraña et al, 2017 ). Their approach was to use the powerful cell-free PMCA (protein misfolding cyclic amplification) technique ( Saborio et al, 2001 ) to determine which mouse-specific substitutions enabled conversion of the naturally resistant rabbit PrP.…”
Section: Purified and In Vitro Models Of Resistantmentioning
confidence: 99%